Hegemoni Neoliberalisme dalam Konten Finfluencer: Analisis Wacana Kritis Owner vs. Owned dalam Video Youtube Timothy Ronald: Neoliberal Hegemony in Finfluencer Content: A Critical Discourse Analysis of Owner vs. Owned in Timothy Ronald’s YouTube Video - Rizky, JH. Fahrizal Nur (Journal of Literature and Education, 2025)
This This study reveals the construction of discourse and ideology in the content of a popular Indonesian financial influencer (finfluencer) through a case study of Timothy Ronald’s YouTube video titled “You Don’t Have Time” (Kalian Gak Punya Waktu). Employing Teun A. van Dijk’s Critical Discourse Analysis (CDA) model, which integrates the analysis of text, social cognition, and social context dimensions, this research aims to uncover the mechanisms of persuasive discourse production behind the content. Analysis of the text dimension demonstrates the use of future crisis narrative strategies and binary polarization contrasting the superior “Owner” group with the inferior “Owned” group. In the dimension of social cognition, the study finds a reproduction of a capitalist mentality that reduces humans to cost variables. Meanwhile, within the social context dimension, the discourse is identified as exploiting the economic vulnerability of Generation Z to instill an ideology of radical individualism and the glorification of hustle culture. The research concludes that the content serves not merely as financial education, but rather as an instrument of value hegemony capitalizing on the anxiety of young audiences.